Nutritional assessment of adolescents: A cross-sectional study from public schools of North India. - Sandeep Kaur; Rajesh Kumar; Manmeet Kaur (PLoS ONE)
Background Technological advancements and globalization have shifted dietary behaviours, contributing to increased chronic disease prevalence in Low- and Middle-Income Countries (LMICs) like India. Adolescents are particularly vulnerable due to these changes, which can impact their lifelong health. This study aimed to assess the nutritional status of adolescents in public schools in Chandigarh, India. Methodology Conducted as part of a cluster randomized control trial, the study used two-stage random sampling to select 12 schools and eighth-grade classes, recruiting 453 adolescents aged 10-16 years. Nutritional status was evaluated through dietary behaviour assessments, anthropometric measurements, and 24-hour urinary salt-level analysis. Dietary patterns were recorded using two 24-hour recalls, and analyzed with PURE study software based on 2010 Indian dietary data from ICMR-NIN. Anthropometric measures followed standardized protocols, and salt levels were assessed in laboratories. Results The mean age of the adolescents was 13.06 years, with 55% being boys. Among them, 32% had high salt intake, and 55% had high sugar intake. Additionally, 90% had low fruit intake, and 83% had low vegetable intake. The adolescents were deficient in several macro and micronutrients, including energy, fats, fibre, iron, zinc, iodine, riboflavin, and vitamins B-6 and B-12. A higher proportion of boys (10%) were classified as thin compared to girls (2%), while a greater proportion of girls (36%) had abdominal obesity. In contrast, a larger proportion of boys (23%) were severely acutely malnourished. Nearly all adolescents exhibited high urinary excretory salt levels. Conclusion Most adolescents exhibited dietary risk factors, including high salt and sugar intake, along with low consumption of fruits and vegetables. Many were deficient in various macro and micronutrients, with the coexistence of both thinness and obesity. Regular nutritional assessments in schools are essential to address the dual burden of undernutrition and overnutrition. Furthermore, health-promoting interventions should be developed within school settings to encourage healthy dietary practices.